Snake Venom in Context: Neglected Clades and Concepts - Jackson, Timothy N. W.; Jouanne, Hadrien; Vidal, Nicolas (Frontiers in Ecology and Evolution, 2019)
Despite the fact that venom is an intrinsically ecological trait, the ecological perspective has been widely neglected in toxinological research. This neglect has hindered our understanding of the evolution of venom by causing us to ignore the interactions which shape this evolution, interactions that take place between venomous snakes and their prey and predators, as well as among conspecific venomous snakes within populations. In this opinion piece, we introduce and briefly discuss several ecologically oriented concepts that may be of interest to toxinologists, before reviewing a range of non-front-fanged snake taxa that have been neglected toxinologically, but which represent the majority of extant ecological diversity amongst snakes. We conclude by noting that the ecological perspective even has something to offer to clinical toxinology, in the wake of the World Health Organization reinstating snakebite envenoming to its list of Neglected Tropical Diseases.